VD_FINDINFO HC / 2016 / 389 vom 4. April 2016 - VD Tribunal cantonal (2016)
DÉCISION D'IRRECEVABILITÉ, VICE DE FORME, OBSERVATION DU DÉLAI, MOTIVATION DE LA DEMANDE | 132 al. 1 CPC (CH), 321 al. 1 CPC (CH)